Integrated prosumers–DSO approach applied in peer-to-peer energy and reserve tradings considering network constraints. (1st July 2022) - Botelho, D.F.; de Oliveira, L.W.; Dias, B.H.; Soares, T.A.; Moraes, C.A.
Abstract: In recent years, there has been an increase of Renewable Energy Sources (RES) in energy markets that has to lead their agents to become more proactive. In this scenario, a market structure based on Peer-to-Peer (P2P) transactions is very promising but presents challenges for the network operation. A critical challenge is to ensure that network constraints are not violated due to energy trades between peers and neither due to the use of reserve capacity. In this paper, it is proposed a new iterative sequential approach for energy and reserve P2P market that ensures the feasibility of both energy and reserve transactions under network constraints. The methodology considers the interaction between the prosumers and the Distribution System Operator (DSO) in making the final market/operation decision and can be integrated into the existing distribution system. The proposed approach includes the estimation of reserve requirements based on the RES uncertain behavior from historical generation data, which allows identifying RES patterns. The proposed model is assessed through a case study that uses a 14-bus system, under the technical and economic criteria. The results show that the approach can ensure a feasible network operation encompassing energy and reserve markets. Highlights: An optimization approach to integrate prosumer and DSO for energy and reserve market solution. Inclusion of electrical network constraints into the energy and reserve market problem. Obtaining feasible results under both the energy and electrical network constraints. Modeling uncertainties over distributed renewable energy sources through historical generation data. Evaluation of the reserve calculation from two probabilistic algorithms.